Life Cycle Assessment of PEEK for Additive Manufacturing - Bernardino, Jorge Miguel Agostinho (2022)
The lifecycle assessment process (LCA) is a method that allows one to determine the environ- mental impact and gives the information needed to improve the environmental performance of processes which allows for reducing the human footprint in the environment. This dissertation consists of a lifecycle assessment of the production of polyetheretherketone (PEEK) in both the additive manufacturing and injection molding processes with the aim of selecting the most environmentally friendly process. This assessment is made considering a cradle-to-grave approach from when the natural resources are extracted until the final piece is discarded. This analysis is supported using LCA databases and real experimental data collected at NOVA School of Science and Technology. This data will allow for a more conscious choice in selecting one manufacturing process over the other. OpenLCA was the selected software to perform the life cycle assessment with Delft's University of Technologies' IDEMAT database. It was determined that the additive manufacturing production of PEEK is the manufacturing method that contains the least environmental impact mainly because of the reduction of travel distances that are associated with more local production. This compensates for the slight in- crease in energy consumption of additive manufacturing compared to the injection molding process.